Analysis of Sharia Marketing Strategies in Micro Businesses - Rozikin, Khoirul; Musthofa, M. Arif; Nurjali, Nurjali (CV. Zabags Qu Publish, 2025)
This study discusses the analysis of sharia marketing strategies in micro-businesses, with a focus on the application of Islamic values in marketing activities. Microbusinesses have an important role to play in the economy, but they face challenges such as limited capital, market access, and a lack of understanding of effective marketing strategies. Sharia marketing offers solutions through the principles of honesty, fairness, and transparency that can increase customer loyalty and business competitiveness. The research method used is a qualitative approach with a case study method. Data was collected through in-depth interviews, direct observations, and documentation analysis. The results of the study show that sharia marketing strategies have a positive impact on the sustainability of micro businesses. Traders who apply the principles of honesty and transparency in transactions have an easier time gaining customer trust. However, the implementation of sharia marketing still faces various obstacles, including a lack of in-depth understanding of this concept as well as limited capital. Therefore, education, financial support, and the use of digital technology are important steps in increasing the effectiveness of sharia marketing. This research confirms that sharia marketing has great potential in building sustainable and ethical micro businesses. Support from various parties, including Islamic financial institutions and the government, is needed to strengthen the implementation of this strategy. Further research is suggested to explore sharia-based marketing innovations in various business sectors.